The importance of controlling the purchasing function in increasing the profitability of the industrial enterprise Case study of the industrial complex “ALFADITEX” in Béjaia - bouriche, mhenni (Journal of Research in Finance and Accounting, 2023)
This study aims to shed light on the purchasing function, as it is an important and fundamental factor in defining and achieving the enterprise’s strategy, and to highlight the importance of controlling it in increasing the enterprise’s profitability by applying it to the “ALFADITEX” industrial complex in Béjaia. This study concluded that the efficiency of the purchasing function in managing the resources of the enterprise under study contributed significantly to increasing its profitability, as there are rarely investments with that level of return, especially in the short term.